PENGARUH CURRENT RATIO (CR) DAN DEBT TO ASSET RATIO (DAR) TERHADAP HARGA SAHAM PADA PT. BENTOEL INTERNATIONAL INVESTAMA TBK. TAHUN 2013-2022 - Susanto; Dijan Mardiati (Journal of Research and Publication Innovation, 2024)
The purpose of this study was to determine the effect of Current Ratio and Debt to Asset Ratio on the Share Price of PT Bentoel International Investama Tbk during the period 2013-2022. The research method and type of data used in this study are descriptive quantitative and secondary data in the form of financial statements. The analysis used in this study used the SPSS V.27 test tool. In this study, the data analysis methods used were descriptive analysis test, classical assumption test, multiple linear regression and hypothesis testing. The results of the analysis show that partially, there is no significant influence between Current Ratio on Stock Price. Likewise with the Debt to Asset Ratio, which also has no significant effect partially on the company's Stock Price. Simultaneously, the two variables also have no significant effect on the Share Price of PT Bentoel International Investama Tbk. The implications of these findings support the importance of other factors that may affect stock prices in the capital market, as well as highlighting the complexity of understanding the factors that influence the valuation of company shares.